Inflammatory myofibroblastic tumor in the liver after bone marrow transplantation: case report and literature review - Yang, Shuhui; Tang, Yongsheng; Yuan, Zenan; Zhang, Jianwen (Frontiers in Medicine, 2025)
IntroductionInflammatory myofibroblastic tumor (IMT) is a rare low-grade malignant neoplasm in the liver. Timely diagnosis and treatment of IMT are challenging due to its atypical symptoms and imaging results.Case reportWe report a 46-year-old woman who presented to our hospital with persistent hyperpyrexia and discomfort in the right upper abdomen for 2 months post bone marrow transplantation. Radiological findings revealed a space-occupying lesion of uncertain nature in the liver. Since the histological examination of the biopsy specimen indicated IMT, she underwent surgical resection. Subsequently, the postoperative pathology confirmed the diagnosis of IMT. The patient’s febrile condition subsided after the surgery. A magnetic resonance imaging (MRI) scan performed 8 months later showed no signs of recurrence.ConclusionIMTs are caused by genetic rearrangements. Diagnosing IMT can be challenging especially in this case as we had to differentiate the tumor from inflammatory diseases associated with bone marrow transplantation. Hence, a thorough pathological immunohistochemical examination is required to confirm its diagnosis. Local IMTs should be treated with radical surgical resection. In cases of distant metastasis or incomplete resection cases, chemotherapy, targeted therapy, or immunotherapy can be utilized. Regular follow-up is crucial for improving the patient’s survival rate.